Getting countries alternative to resolve supply chain management regarding wheat commodity for Indonesia during war between Ukraine and Russia - Giri Nurpribadi; Erina Rulianti (Privietlab, 2022)
International Business is a management to entering International among some countries with international trade activities and macroeconomics indicator in more than one country.Supply Chain Management is the process of managing movement of , information, raw material,money in the organization system.Supply chain practices are not only important in local business but also in global business between one country to another country.The Effect of Globalization,past history, politics power and military power had been dominated international relations. War event between Russia and Ukraine.Meanwhile, relevant with brainly globalization, power subsystem ,had been stressed from through economic scope and culture circumstances. Until now,the strength of every country depends on abilities and capacity these country for supply chain management.The aims of research is to analysis about influence between Wheat Import to Cost Insurance Freight from Ukraine. Every activities need delivery,and every delivery had been determined payment systems.Next Purposes is to search other countries outside Russia and Ukraine to access some countries which wheat very available. The research methods is a quantitative research, purpose is to explains about overall problem solving regarding supply chain management.Specific case with Invasion Problems. Invasion as a specific problem adjustment with international relations. Trend international relations with example invasion from Russia toward Ukraina.Since February 24, 2022 all weapon technology will be prepare for defence each every country.Embargo for Ukraina transactions and Rusia transaction,inside and outside. People still damages,because international transaction with Ruble currency. Some people will be conversion from US for Cost Insurance Freight as an International unit measurement for douane system payments for cost of good sold, transportation cost,insurance for the end of seaport aim. Conclusion of the quantitative research is a statement for Supply Chain Management with implications for currency,and also international business environment,and effort for gained with balance terms of trade in other countries. Statistics with t counted = 24.291 and F counted = 590.045 as a process , whereas to imply significant analysis to get correlation for douane payments,because t table = 12.706 ,and F Table = 240.120,data especially for Russia t counted : 24.030.